Remote training as a common tool for the different professionals involved in the acute phase after terror attacks across Europe: Perspectives from an expert panel - Askenazy, Florence; Fernandez, Arnaud; Altan, Levent; Battista, Michèle; Dückers, Michel; Gindt, Morgane; Nachon, Ophélie; Ivankovic, Aleksandra; Porcar-Becker, Ingeborg; Prieto, Nathalie; Robert, Philippe; Stene, Lise Eilin; et al. (Frontiers in Psychiatry, 2022)
The acute response after a terror attack may have a crucial impact on the physical and psychological wellbeing of the victims. Preparedness of the professionals involved in the acute response is a key element to ensure effective interventions, and can be improved through trainings. Today in Europe there is a recognized lack of inter-professional and international trainings, which are important, among others, to respond to the needs and the rights of victims affected by a terrorist attack in another country than their home country. In this paper we report the perspectives of an expert panel composed by different categories of professionals on the possible role of interprofessional trainings provided remotely. The experts discussed the pertinence of remote trainings for professionals involved in the acute response of a terror attack, and highlighted their Strengths, Weaknesses, Opportunities and Threats (SWOT analysis). We concluded that, while remote trainings cannot replace in-person trainings, they may be useful to share knowledge about the role and the organization of the different categories of professionals, thus potentially improving response coordination, and to easily share good practices across professionals and countries.